14-Deoxyandrographolide desensitizes hepatocytes to tumour necrosis factor-alpha-induced apoptosis through calcium-dependent tumour necrosis factor receptor superfamily member 1A release via the NO/cGMP pathway - Roy, DN (Blackwell Publishing Ltd, 2010)
BACKGROUND AND PURPOSE: Andrographis paniculata (AP) has been found to display hepatoprotective effect, although the mechanism of action of the active compounds of AP in this context still remains unclear. Here, we evaluated the hepatoprotective efficacy of 14-deoxyandrographolide (14-DAG), a bioactive compound of AP, particularly its role in desensitization of hepatocytes to tumour necrosis factor-alpha (TNF-α)-induced signalling of apoptosis. EXPERIMENTAL APPROACH: TNF-α-mediated ligand receptor interaction in hepatocytes in the presence of 14-DAG was studied in vitro in primary hepatocyte cultures, with the help of co-immunoprecipitation, confocal microscopy and FACS analysis. Events associated with 14-DAG-induced TNFRSF1A release from hepatocytes were determined using immunoblotting, biochemical assay and fluorimetric studies. Pulse-chase experiments with radiolabelled TNF-α and detection of apoptotic nuclei by terminal transferase-mediated dUTP nick-end labelling were performed under in vivo conditions. KEY RESULTS: 14-DAG down-regulated the formation of death-inducing signalling complex, resulting in desensitization of hepatocytes to TNF-α-induced apoptosis. Pretreatment of hepatocytes with 14-DAG accentuated microsomal Ca-ATPase activity through induction of NO/cGMP pathway. This resulted in enhanced calcium influx into microsomal lumen with the formation of TNFRSF1A–ARTS-1–NUCB2 complex in cellular vesicles. It was followed by the release of full-length 55 kDa TNFRSF1A and a reduction in the number of cell surface TNFRSF1A, which eventually caused diminution of TNF-α signal in hepatocytes. CONCLUSION AND IMPLICATION: Taken together, the results demonstrate for the first time that 14-DAG desensitizes hepatocytes to TNF-α-mediated apoptosis through the release of TNFRSF1A. This can be used as a strategy against cytokine-mediated hepatocyte apoptosis in liver dysfunctions.